Remarks on the policy of the Bolshevik authorities towards the Catholic Church in the former eastern borderlands of the Republic of Poland in the years 1917–1922 (until the proclamation of the USSR) - Patek, Artur (Balcanica Posnaniensia. Acta et studia, 2001)
The article addresses the policy of the Bolshevik authorities toward the Catholic Church in the territories of the former eastern borderlands of the Polish-Lithuanian Commonwealth during the first years following the Russian Revolution. The aim of the study is to demonstrate the mechanisms of Bolshevik religious policy and its impact on the functioning of the Catholic Church up to the establishment of the Soviet Union. The author employs a historical method based on the analysis of church documents, administrative materials, and literature concerning Soviet religious policy. The article presents the organizational structure of the Church in Belarus and Ukraine and the scale of its presence in the early 1920s. The author points out that the authorities’ actions included restricting religious activity, confiscating church property, persecuting clergy, and attempting to eliminate the Church’s influence from social life. The conclusions emphasize that the years 1917–1922 shaped the fundamental principles of Soviet religious policy, the objective of which was the gradual weakening and marginalization of the Catholic Church in territories incorporated into the Bolshevik state.